Answer:
d. 11.6
Step-by-step explanation:
The results of the first die and the second one are independent to each other. The expected value of Z is obtained, therefore, by summing the expected values of both X and Y, because Z = X+Y and X and Y are independent. As a result 
Answer:
vertical translation of 3 units down
Step-by-step explanation:
we have
----> the parent function
The vertex of f(x) is the point (0,0)
----> the transformed function
The vertex of g(x) is the point (0,-3)
so
The rule of the translation is
f(x) -----> g(x)
(0,0) ----> (0,-3)
(x,y) ----> (x,y-3)
That means ---> The translation is 3 units down
see the attached figure to better understand the problem
m = -1
Step-by-step explanation:
-16m = 7 + 9
-16m = 16
m = 16 ÷ -16
m = -1